Counterexamples to Strichartz estimates for the kinetic transport equation based on Besicovitch sets - Ovcharov, Evgeni Y. (Nonlinear analysis. Theory, methods & applications, 2011)
We show that the Strichartz estimates for the kinetic transport equation containingLx∞-norms in the spatial variables x fail on the characteristic functions of Besicovitch sets.
Available online: 22 December 2010
Gesehen am 29.05.2018